Identification of factors influencing NVIDIA stock price - Valavin, Denis (2024)
This bachelor's thesis investigates the impact of investor attention on the excess returns of Nvidia's stock. As sources of information on investor attention, I selected data from Google Trends and Wikipedia Pageviews. The search queries were chosen to include not only the company's name but also terms closely related to its business. The relationship between excess returns and increased market interest was estimated using linear regression. Another objective of the study was to determine whether the company's stock exhibits the selected market anomaly, post-earnings-announcement drift. This was analysed through changes in Cumulative Abnormal Returns.